Lusitanian language and onomastics of Lusitania: 25 years later (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
The aim of this paper is to review the novelties of the last 25 years in epigraphy and onomastics of the western Hispanic area. Time has made possible to help outline geographically each of the three linguistic areas in which the region is divided: the Lusitanian (or Lusitano-Galician), the Celtiberian and the southwestern writing.
Keywords: Western Hispania, Lusitanian, onomastics, Celtici from SW, language from SW.